Implementation of Multicultural Education at SMP 01 Tanjung Balai - Elysa, Elysa; Ifanka Lubis, Vina (Educate: Jurnal Ilmu Pendidikan dan Pengajaran, 2022)
The purpose of making this journal is to find out the implementation of multicultural education at SMP 1 Tanjung Balai and to find out the supporting and inhibiting factors in implementing multicultural education at SMP 1 Tanjung Balai. This study uses a qualitative method, with the type of descriptive research. Data collection techniques using observation, and interviews. The data analysis technique used is descriptive qualitative analysis. The results showed that SMP 1 Tanjung Balai has a very multicultural nuance. And it can be seen that SMP 1 Tanjung Balai has implemented multicultural education in the school environment since the beginning.